Urbanization and Social Structure Transformation in Indonesia: A Critical Review of BPS and UN-Habitat Reports - Agus Kusman; Yola Mutia Damayanti (Anthroposia: Journal of Social and Human Development, 2026)
Rapid urbanization in Indonesia has intensified debates on how spatial expansion reshapes social organization, inequality, and governance capacity, yet institutional reports often present growth as a technical development trajectory rather than a structural social transformation. This study critically examines how urban change is constructed within official narratives produced by Badan Pusat Statistik and UN-Habitat, asking how statistical framing influences interpretations of social structure. Employing a non-empirical qualitative design, the research conducts a critical document-based review using discourse analysis, comparative policy reading, and socio-spatial interpretation of institutional reports published over the last fifteen years. The findings indicate that demographic concentration, housing provision, and infrastructure expansion dominate institutional narratives, while relational dimensions such as social cohesion, informal networks, and distributive inequality remain underrepresented. This imbalance shapes policy discourse by privileging technocratic planning logics and narrowing the conceptualization of urban transformation. The study concludes that urbanization in Indonesia operates not only as a spatial process but also as a knowledge-production regime in which measurement practices influence governance priorities and social outcomes, highlighting the need for more reflexive integration of social theory into urban policy analysis.